Knowledge related to nutrition and hypertension management practices of adults in Ga-Rankuwa day clinics - N.G. Nkosi; S.C.D. Wright (AOSIS, 2010)
Hypertension is a global, non-communicable chronic disease being asymptomatic and known as the silent killer with signs and symptoms only occurring when a target organ is damaged. Being a condition common in South Africa, hypertension is also a risk factor for cerebro-vascular incidents, myocardial infarction, left ventricular hypertrophy, renal disease and retinopathy. Black adults in an urban environment appear to be especially vulnerable to excessive increases in blood pressure. The research question explored was what was the knowledge of hypertensive adults attending day clinics in Ga-Rankuwa regarding nutrition and hypertension management practices. An exploratory strategy was used as no similar research had previously been conducted in Ga-Rankuwa. A cross sectional survey design was used to investigate hypertensive adults attending the three primary health clinics in Ga-Rankuwa. The sampling method was convenient and the sample size 101 participants. Two data gathering methods were used, these being physical measurements and self-report. For the self-report, a structured interview was conducted. The data were analysed using descriptive statistics. The results indicated a lack of knowledge regarding nutrition and management of hypertension. The proportion of participants with uncontrolled hypertension was high (58.6%) and non-compliance with medication occurred frequently (58.1%). A third (28.7%) of the sample lacked knowledge of the complications of hypertension (28.7%). A community-based intervention, based on the results of the study, is recommended.